Successful pregnancy following aplastic anaemia. - Leong, K.W.; Teh, A.; Bosco, J.J.; Lim, J. (1995)
Pregnancy following idiopathic aplastic anaemia is rare and is difficult to manage because of life-threatening episodes of bleeding and infections. Only a handful of cases has been reported in the literature. The pregnancies were unsuccessful in the majority. The present report describes a patient with moderately severe idiopathic aplastic anaemia who was managed with intensive haematological support leading to delivery of a healthy infant by caesarean section. Despite platelet transfusion refractoriness as a result of transfusions prior to pregnancy, adequate platelet transfusions prevented excessive bleeding. The literature is reviewed and management with platelet transfusions is discussed.